Optimization Of Population And Concentration Of Liquid Organik Fertilizer On Growth And Production Of Sweet Corn (Zea mays saccharata Strut) - Wiwit Widiarti; Iskandar Umarie; Insan Wijaya; Yohan Dita Nugroho (International Applied Science, 2022)
: Sweet corn (Zea mays saccharata Strut) is a weel-known horticultural commodity and has been cultivated in various processed forms. Marked demand for sweet corn continues to increased, so market needs continue to grow and need to be maximized. This study aims to determine population optimization and concentration of liquid Organic fertilizer on the growth and production of sweet corn (Zea mays saccharata Strut). This study used a Factorial Randomized Block Design with 3 replications and consited of 2 factors. The first factor is population difference, P1:population 62,000 plant per hectare, P2: population 83,333 plant per hectare, P3:125,000 plant per hectare, while the second factor is concentration of liquid organic fertilizer, N1:without POC, N2:POC 45 ml/L, N3:POC 90 ml/L, N4:POC 135 ml/L. Differences in population significanly affected the parameters of plant height 42 DAP, stemp diameter 42 DAP, lenght of cob, diameter of cob, weight of cob. The best treatment of was obtained in the P1 treatment, which was 62,000 plant per hectare. NASA POC concentration significantly affected all parameters. The best treatment was obtained in the N4 treatment with a concentration ot 135 ml/L. The interaction between population differences and NASA POC concentration had a significant effect on the parameters of plant height at 42 DAP.